Understanding teacher educators’ perceptions and practices about ICT integration in teacher education program - Ngao, Ayubu I, Sang Guoyuan and Kihwele, Jimmy E. (Education Technology and Literacies: State of the Art), 2024)
A research article submitted to the Education Technology and Literacies: State of the Art) journal 2022.